2021
DOI: 10.1007/s11239-021-02536-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of prothrombin complex concentrate in the management of oral factor Xa inhibitors associated major bleed assessed by ISTH and ANNEXA-4 criteria

Abstract: Direct oral anticoagulants (DOACs) are increasingly used for stroke prevention in atrial fibrillation and treatment and prevention of venous thromboembolism. They are also associated with bleeding risk. Existing literature suggests that prothrombin complex concentrate (PCC) administration may help control bleeding due to factor Xa inhibitors (FXaI). To determine the hemostatic efficacy of PCC in patients with major bleeding due to FXaI, we performed a retrospective chart review of 50 patients who presented wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Several other smaller studies have shown the use of 4F-PCCs as a viable reversal option for DOAC-related ICH for anticoagulation reversal (reversal rates, 54.5%-94.7%) and safety (mortality rates, 4.7%-63.6%; thrombotic event rate, 0%-17.2%). 8 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 Albeit with significant heterogeneity, our meta-analysis found a combined proportion of anticoagulation reversed of 77%, a mortality rate of 26%, and a thromboembolic event rate of 8% ( Figures 1 - 3 ).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Several other smaller studies have shown the use of 4F-PCCs as a viable reversal option for DOAC-related ICH for anticoagulation reversal (reversal rates, 54.5%-94.7%) and safety (mortality rates, 4.7%-63.6%; thrombotic event rate, 0%-17.2%). 8 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 Albeit with significant heterogeneity, our meta-analysis found a combined proportion of anticoagulation reversed of 77%, a mortality rate of 26%, and a thromboembolic event rate of 8% ( Figures 1 - 3 ).…”
Section: Discussionmentioning
confidence: 72%
“…Thirty-six studies were included in the meta-analysis (eAppendix 1 in the Supplement ). Twenty-two studies with 967 participants evaluated 4F-PCC for reversal 8 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ; 17 studies with 525 participants evaluated AA 13 , 35 , 36 , 37 , 39 , 40 , 41 , 42 , 44 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ; and 5 studies with 340 participants evaluated idarucizumab, 12 , 53 , 54 , 55 , 56 consisting of a total of 1832 patients with ICH while receiving treatment with a DOAC. Eight studies had data on more than 1 agent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Andexanet alfa is an inactive recombinant factor Xa, and in the ANNEX-4 study (27), 80% of patients with acute major bleeding (intracranial or gastrointestinal) secondary to an oral DFXaI, achieved improved hemostatic function with administration of andexanet alfa. The reversal agent is expensive and not readily available in many institutions, with prothrombin complex concentrates (PCCs) being an alternative therapy (28).…”
Section: Rivaroxabanmentioning
confidence: 99%
“…Andexanet alfa is an inactive recombinant factor Xa, and in the ANNEX-4 study ( 27 ), 80% of patients with acute major bleeding (intracranial or gastrointestinal) secondary to an oral DFXaI, achieved improved hemostatic function with administration of andexanet alfa. The reversal agent is expensive and not readily available in many institutions, with prothrombin complex concentrates (PCCs) being an alternative therapy ( 28 ). As there are no current pediatric specific data on its use, a recent survey of pediatric hematologists found a 44% preference for the use of andexanet alfa in pediatric patients requiring reversal for acute life threatening bleed due to FXaI, with 55% choosing PCCs ( 29 ).…”
Section: Rivaroxabanmentioning
confidence: 99%